The Influence of Attitude, Subjective Norm and Perceived Behavioral Control towards Organic Food Purchase Intention - Hana Novita Hasan; Sentot Suciarto (Soegijapranata Catholic University, 2020)
This study aims to determine the determinants of intention in buying organic food. This thesis focuses on the consumer of organic food products in Indonesia who use online media in Instagram to make their organic food purchases with Theory of Planned Behavior. The data collection in this study was conducted in two stages, namely pre-survey to analyze opinion leaders and types of organic foods that will be used as a limitation of the study and the second stage is the research questionnaire. The analysis technique used is qualitative data analysis. Based on the results of the study conclusions can be drawn as follows: adherence to organic food and perceived behavioral control significantly influence buying intention in organic food, while subjective norms are found to have no significant effect on buying intention in organic food. Attitudes toward organic food have the strongest influence among the other two variables. Subjective norms have the lowest influence. Subjective norms or pressure from other people to consume organic food apparently do not have a significant effect because it does not originate from oneself (external) or is not their own volition, in contrast to the attitude and perceived behavior control variables that originate from oneself.